Advancing Public Health Policy in Louisiana Through Evidence-Based Strategies: Successes and Opportunities. Issue 1 (January 2019) - Poole, Mary Kathryn; Mundorf, Adrienne R.; Englar, Naomi K.; Rose, Donald
In 2013, a team of public health professionals at Tulane University launched a project to explore strategies for shaping a healthier Louisiana. The team investigated methods for improving diet and physical activity behaviors in early childhood, school, and community settings that could be translated into specific policies. Through key informant interviews and scans of academic journals and reports issued by public health agencies, the team generated a set of actionable steps that could increase healthful behaviors. Previous efforts to address similar topics in Louisiana and other states, and their reception from policy makers, were also considered during analysis. Subsequently, a state legislator used the team's work to introduce public health legislation in 2014. The legislation led to a number of incremental changes in state policy and resolutions for additional policy-relevant studies. This case study summarizes the promising physical activity and nutrition strategies that were considered by the Tulane team, how the team's work product was integrated into state legislation, the outcomes of the legislation, and a set of recommendations for how Louisiana can expand on this work. This article demonstrates how the work of public health professionals can have a positive influence on the policy-making process through research and education.